Volcanic Gas Emissions Along the Colombian Arc Segment of the Northern Volcanic Zone (CAS‐NVZ): Implications for volcano monitoring and volatile budget of the Andean Volcanic Belt. (14th November 2019) - Lages, J.; Chacón, Z.; Burbano, V.; Meza, L.; Arellano, S.; Liuzzo, M.; Giudice, G.; Aiuppa, A.; Bitetto, M.; López, C.
Abstract: Studying spatial and temporal trends in volcanic gas compositions and fluxes is crucial both to volcano monitoring and to constrain the origin and recycling efficiency of volatiles at active convergent margins. New volcanic gas compositions and volatile fluxes are here reported for Nevado del Ruiz, Galeras, and Purace, three of the most persistently degassing volcanoes located in the Colombian Arc Segment of the Northern Volcanic Zone. At Nevado del Ruiz, from 2014 to 2017, plume emissions showed an average molar CO2 /ST ratio of 3.9 ± 1.6 (ST is total sulfur, S). Contemporary, fumarolic chemistry at Galeras progressively shifted toward low‐temperature, S‐depleted fumarolic gas discharges with an average CO2 /ST ratio in excess of 10 (6.0–46.0, 2014–2017). This shift in volcanic gas compositions was accompanied by a concurrent decrease in SO2 emissions, confirmed on 21 March 2017 by high‐resolution ultraviolet camera‐based SO2 fluxes of ~2.5 kg/s (~213 t/day). For comparison, SO2 emissions remained high at Nevado del Ruiz (weighted average of 8 kg/s) between 2014 and 2017, while Puracé maintained rather low emission levels (<1 kg/s of SO2, CO2 /SO2  ≈ 14). We here estimate carbon dioxide fluxes for Nevado del Ruiz, Galeras, and Puracé of ~23, 30, and 1 kg/s, respectively. These, combined with recent CO2 flux estimates for Nevado del Huila of ~10 kg/s (~860 t/day), imply that this arc segment contributes about 50% to the total subaerial CO2 budget of the Andean Volcanic Belt. Furthermore, our work highlights the northward increase in carbon‐rich sediment input into the mantle wedge via slab fluids and melts that is reflected in magmatic CO2 /ST values far higher than those reported for Southern Volcanic Zone and Central Volcanic Zone volcanoes. We estimate that about 20% (~1.3 Mt C/year) of the C being subducted (~6.19 Mt C/year) gets resurfaced through subaerial volcanic gas emissions in Colombia (Nevado del Ruiz ~0.7 Mt C/year). As global volcanic volatile fluxes continue to be quantified and refined, the contribution from this arc segment should not be underestimated. Key Points: A new report on volcanic gas compositions and volatile fluxes for three of the most persistently active volcanoes in the CAS is presented We estimate that subaerial emissions from CAS volcanoes contribute about 50% to the total subaerial CO2 budget of the Andean Volcanic Belt Our work highlights the distinct magmatic CO2 /ST signatures of Andean volcanoes, with emphasis on its northward increase and relation to along‐arc variations in carbon‐rich sediment input